Procyclicality and fair value accounting - Novoa, Alicia; Scarlata, Jodi G.; Solé, Juan (IMF working paper, 2009)
In light of the uncertainties about valuation highlighted by the 2007-2008 market turbulence, this paper provides an empirical examination of the potential procyclicality that fair value accounting (FVA) could introduce in bank balance sheets. The paper finds that, while weaknesses in the FVA methodology may introduce unintended procyclicality, it is still the preferred framework for financial institutions. It concludes that capital buffers, forward-looking provisioning, and more refined disclosures can mitigate the procyclicality of FVA. Going forward, the valuation approaches for accounting.